Candidatus Phytoplasma asteris' strains associated with oil palm lethal wilt in Colombia - Álvarez, E.; Mejía, Juan Fernando; Contaldo, N.; Paltrinieri, S; Duduk, B; Bertaccini, A (2014)
Full text article is the author's version